Optimalisasi Lahan Rawa Lebak Mendukung Produsi Padi di Kabupaten Batanghari Jambi - Busyra Buyung Saidi; Hendri Purnama; Jon Hendri; Firdaus Firdaus; Nur Imdah Minsyah (Seminar Nasional Lahan Suboptimal, 2021)
Saidi BB, Purnama H, Hendri J, Firdaus F, Minsyah NI.  2021. Lebak swamp land optimization supports rice production in Batanghari Jambi Regency. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang  20 Oktober 2021. pp. 58-71. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Lebak swamp land is a swamp that is affected by the presence of inundation with a duration of inundation of more than 3 months and inundation height of more than 50 cm. The potential of lebak swamps for the development of rice farming is very large. The area of lebak swamp land in Batanghari Regency is 4,033 ha. In order to support the Land Optimization Program to increase rice production in Batanghari district, 2,500 ha of lebak swamp land has been established in 7 (seven) sub-districts, 21 villages. The study aims to: (1) provide information about the characteristics, potential, opportunities of lowland swamp land for agricultural development, and (2) provide direction and strategic steps for developing lowland swamp land in Batanghari Regency. The assessment will be carried out from July to August 2021. carried out using a survey method to collect primary data (characteristics of lebak swamp land) and secondary data (other supporting factors that influence the increase in rice production). The results of the study showed that the lowland swamp rice fields in Batanghari Regency were categorized as shallow lowland swamps, with alluvial soil types, namely undeveloped soils, formed from fine, coarse and organic alluvium materials. The results of the evaluation of land suitability for rice plants, the main limiting factors are the availability of oxygen (drainage), nutrient retention and nutrient availability, especially nitrogen, phosphorus and potassium. For this reason, it is necessary to improve irrigation channels and manage land and nutrients (fertilization). The optimization of lebak swamp land management is very likely to be improved by increasing the cropping index (IP) from 100 to 200, introducing new, adaptive varieties, including Inpara3. increase farmers' income.